Financial Literacy, Risk and Time Preferences: Results from a Randomized Educational Intervention - Matthias Sutter; Michael Weyland; Anna Untertrifaller; Manuel Froitzheim (Institute of Labor Economics (IZA), 2020)
We present the results of a randomized intervention in schools to study how teaching financial literacy affects risk and time preferences of adolescents. Following more than 600 adolescents, aged 16 years on average, over about half a year, we provide causal evidence that teaching financial literacy has significant short-term and longer-term effects on risk and time preferences. Compared to two different control treatments, we find that teaching financial literacy makes subjects more patient, less present-biased, and slightly more risk-averse. Our finding that the intervention changes economic preferences contributes to a better understanding of why financial literacy has been shown to correlate systematically with financial behavior in previous studies. We argue that the link between financial literacy and field behavior works through economic preferences. In our study, the latter are also related in a meaningful way to students' field behavior.
Keywords: C93; D14; I21; 330; time preferences; risk preferences; randomized intervention; financial literacy; field experiment